Choosing the optimal method of blood pressure measurement for limited‐resource rural communities in the “Community Health Assessment Program—Philippines” - Guenter, Dale (J Clin Hypertens (Greenwich), 2017)
The Community Health Assessment Program—Philippines (CHAP‐P) is an international collaboration of investigators whose aim is to adapt a previously proven Canadian community‐based cardiovascular awareness and prevention intervention to the Philippines and other low‐middle–income countries. Choosing a method of blood pressure measurement for the research program presents a challenge. There is increasing consensus globally that blood pressure measurement with automated devices is preferred. Recommendations from low‐middle–income countries, including the Philippines, are less supportive of automated blood pressure devices. The value placed on factors including device accuracy, durability, cost, energy source, and complexity differ with local context. Our goal was to support the progress of local policy concerning blood pressure measurement while testing a comprehensive approach to community‐based screening for cardiovascular risk. The authors describe the challenges in making a choice of blood pressure device and the approach to determine optimal method of measurement for our research program.